The potentials, threats and challenges in sustainable development of Penang National Park - Hong, Chern Wern; Chan, Ngai Weng (Environmental Management Society, Malaysia, 2010)
The Penang National Park (PNP) is recognized as an initiative of sustainable development of the Penang State Government. Since the gazettement of the young Penang National Park about 8 years ago, much have yet to be done to fully realize its potentials. These include growing into a world class ecotourism site in tandem with the UNESCO heritage status of Georgetown, to develop into a world class research center, to create sustainable income as a socio-economic contributor to local communities, and to showcase the success of a national park within a highly urbanized island. However, there are threats to PNP such as development pressures due to land scarcity, encroachment of urban and agricultural land use into the park, illegal developments, and apathetic attitude amongst local visitors which have created many environmental issues, problematic solid waste pollution, and infrastructure construction in the park. All these threats need to be addressed in order to ensure sustainable development of the PNP. The challenges include having political will, creating an effective awareness and environmental education system for all stakeholders, develop a sustainable management plan, environmentally-friendly infrastructure, and focusing on ecotourism rather than mass tourism in the PNP